STUDI PERBANDINGAN KARAKTER MAKROSKOPIS DAN MIKROSKOPIS TIGA JENIS PHYLLANTHUS L. - Anshary Maruzy; Dewi Athikah Fatkhul Jannah; Ari Pitoyo; Dyah Subositi (Floribunda, 2020)
Anshary Maruzy, Dewi Athikah Fatkhul Jannah, Ari Pitoyo, Dyah Subositi. 2020. Comparison Study of Macroscopic and Microscopic Characters in Three Species Phyllanthus L. Floribunda 6(4): 154–166. — Many members of the genus Phyllanthus are widely used as raw materials for medicine. Three species of Phyllanthus that are P. amarus Schumach. & Thonn., P. urinaria L., and P. debilis Klein ex Willd. have a lot of similarity. The aims of this study were to compare macroscopic and microscopic characteristics of this three species. Method of microscopic study by embedding paraffin technique. The observed of macroscopic characters are branching types, leaf shape, color of leaf margin, leaf apex type, color & shape of petal, amount of male petal, color & structure of ripe fruit, color of seed. The results of this study showed the specific characteristics of every species. Keywords: characterization, macroscopic, microscopic, P. amarus, P. debilis, P. urinaria.Anshary Maruzy, Dewi Athikah Fatkhul Jannah, Ari Pitoyo, Dyah Subositi. 2020. Studi Perbandingan Karakter Makroskopis dan Mikroskopis Tiga Jenis Phyllanthus L. Floribunda 6(4): 154–166. — Beberapa anggota genus Phyllanthus banyak dimanfaatkan sebagai bahan baku obat. Tiga spesies Phyllanthus yaitu P. amarus Schumach. & Thonn., P. urinaria L., dan P. debilis Klein ex Willd. memiliki morfologi yang hampir sama. Penelitian ini bertujuan mengetahui perbandingan karakter makroskopis dan mikroskopis dari ketiga spesies tersebut. Penelitian mikroskopis menggunakan metode embedding paraffin. Karakter makroskopis yang diamati adalah tipe percabangan, bentuk daun, warna tepi daun, tipe ujung daun, warna & bentuk mahkota bunga, jumlah mahkota bunga jantan, warna & struktur buah masak, warna biji. Hasil penelitian ini menunjukkan karakteristik spesifik setiap spesies.